The March for Moms. Issue 4 (July 2019) - Breedlove, Ginger
Abstract : Maternal mortality in the United States has increased over the past decade. Maternal morbidity and mortality disproportionately affect women of color. Dr. Breedlove, president of the March for Moms, discusses how a maternity action group of volunteers who also are influential national leaders representing diverse professional societies have joined together with a common goal of making maternity care in the United States safe for all women in all settings. The third annual March for Moms rally was held on the National Mall on Saturday May 11, 2019.